- #1

- 48

- 0

Can someone please check over this real quick. I think I’ve solved this problem correctly, but, I’m not sure.

Solve: [tex]2\sin\theta\cos\theta + 2 \sin\theta - \cos\theta -1 = 0 [/tex]

[tex]2 \sin\theta(\cos\theta + 1) -(\cos\theta + 1) = 0 [/tex]

[tex]2 \sin\theta(\cos\theta + 1) = (\cos\theta + 1)[/tex]

[tex]2 \sin\theta = 1[/tex]

[tex]\sin\theta = 1/2[/tex]

[tex]\theta = (\frac{\pi}{6} + k2\pi)\ \mbox {or}\ (\frac{5\pi}{6} + k2\pi) [/tex]

Solve: [tex]2\sin\theta\cos\theta + 2 \sin\theta - \cos\theta -1 = 0 [/tex]

[tex]2 \sin\theta(\cos\theta + 1) -(\cos\theta + 1) = 0 [/tex]

[tex]2 \sin\theta(\cos\theta + 1) = (\cos\theta + 1)[/tex]

[tex]2 \sin\theta = 1[/tex]

[tex]\sin\theta = 1/2[/tex]

[tex]\theta = (\frac{\pi}{6} + k2\pi)\ \mbox {or}\ (\frac{5\pi}{6} + k2\pi) [/tex]

Last edited: